Aprendizagem do conceito de volume: uma proposta didática compartilhada com licenciandos da matemática - Van Der Mer, Ilda Aparecida da Silva (2017)
This work aims at analyzing a didactic proposal for the teaching of the concept of volume the elementary students, having been the same shared with eight students of the subproject Mathematics “PIBID/UFU” in the form of a short course developed on three dates of 90 minutes, this had to rescue the main ideas of the students about the concept of volume as well as to collect their views on the methodology employed. Based on meaningful learning theory of David Ausubel, had for objectives: (a) examine the potential of material presented, consisting of two types of activities: those who, by means of questions, discussions and handling materials aimed at articulating the volume, mass and content, and those that involve problem solving involving comparison, measurement and production of paving stones; (b) analyze the performance of students in the development of activities and (c) analyze their opinions about work. Were used in filming, audio recording, photographic records, the review of the implementation of the string that indicates that the issues and the problems proposed favored the joints necessary for the formation of the concept, and that the material has to be considered as potentially significant for the construction of the concept of volume and can be applied to elementary school students, since the discussions are adapted to their reality.